2019
DOI: 10.25077/ijasc.3.1.12-16.2019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Community’s Willingness to Pay (WTP) for the Protection of Mangroves in Kuala Langsa, Aceh

Abstract: Mangrove, as one of the most unique ecosystems, is a great natural resource potential with high productivity and biodiversity able to adapt to harsh areas between the sea and coast. Its destruction rate is very mild as it is estimated to 1% each year (Ong et al., 1991) and 0.7-3% per year (Pedleton et al., 2012). The destruction of mangrove is usually related with human population density (Alongi, 2002). Widespread mangrove destruction affects the loss of biodiversity and other resources and the functioning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…People need to spend their money to handle the waste that they produced to help improve the environmental conditions in their areas. [48] reported that 112 respondents from Kuala Langsa, Aceh were willing to pay for the mangrove conservation in their area. The average sum of money that respondents in this area willing to pay for mangrove preservation and reparation of degrading mangrove was about RM9.40 per month.…”
Section: A Social Demographic Aspectmentioning
confidence: 99%
“…People need to spend their money to handle the waste that they produced to help improve the environmental conditions in their areas. [48] reported that 112 respondents from Kuala Langsa, Aceh were willing to pay for the mangrove conservation in their area. The average sum of money that respondents in this area willing to pay for mangrove preservation and reparation of degrading mangrove was about RM9.40 per month.…”
Section: A Social Demographic Aspectmentioning
confidence: 99%